Multicenter retrospective analysis regarding the clinical manifestations and treatment results in patients with hairy cell leukemia: twenty‐four year Turkish experience in cladribine therapy. Issue 4 (13th November 2014) - Hacioglu, Sibel; Bilen, Yusuf; Eser, Ali; Sivgin, Serdar; Gurkan, Emel; Yildirim, Rahsan; Aydogdu, Ismet; Dogu, Mehmet Hilmi; Yilmaz, Mehmet; Kayikci, Omur; Tombak, Anil; Kuku, Irfan; et al.
Abstract: In this multicenter retrospective analysis, we aimed to present clinical, laboratory and treatment results of 94 patients with Hairy cell leukemia diagnosed in 13 centers between 1990 and 2014. Sixty‐six of the patients were males and 28 were females, with a median age of 55. Splenomegaly was present in 93.5% of cases at diagnosis. The laboratory findings that came into prominence were pancytopenia with grade 3 bone marrow fibrosis. Most of the patients with an indication for treatment were treated with cladribine as first‐line treatment. Total and complete response of cladribine was 97.3% and 80.7%. The relapse rate after cladribine was 16.6%, and treatment related mortality was 2.5%. Most preferred therapy (95%) was again cladribine at second‐line, and third line with CR rate of 68.4% and 66.6%, respectively. The 28‐month median OS was 91.7% in all patients and 25‐month median OS 96% for patients who were given cladribine as first‐line therapy. In conclusion, the first multicenter retrospective Turkish study where patients with HCL were followed up for a long period has revealed demographic characteristics of patients with HCL, and confirmed that cladribine treatment might be safe and effective in a relatively large series of the Turkish study population. Copyright © 2014 John Wiley & Sons, Ltd.